A study of fractional TB model due to mycobacterium tuberculosis bacteria. (December 2021) - Kumar, Sunil; Chauhan, R.P.; Momani, Shaher; Hadid, Samir
Highlights: This paper focuses to analyse the fractional TB model. We extend the proposed TB infection model with nonlocal and non-singular operator. We utilize a concept of fractional operator to reformulate the fractional TB model. We conclude that the idea of fractional provides better results. Abstract: The main purpose of the proposed work is to study a TB infection model under incomplete treatment numerically and identify potential infection dynamics. We use the arbitrary-order Caputo-Fabrizio (CF) and Atangana-Baleanu (AB) derivatives to extend the classical TB infection model into a non-classical model. In addition, through fixed-point results, the existence and uniqueness of solutions for the arbitrary order TB model are discussed. We illustrate computational techniques from existing literature for the numerical solutions of the mentioned fractional models. The numerical simulations are presented using MATLAB software with various choices of the fractional-order parameter.